Memórias de um curso de formação de professores de Matemática no Instituto Superior de Ciências da Educação de Cabinda/ Angola (1998-2009) - Ines Florinda Luis Buissa (2016)
This thesis focuses on our understanding of the process of formation of mathematics teachers at a higher level in the course of Educational Sciences, Mathematics option, offered by the Institute of Educational Sciences (ISCED) in Cabinda, Angola, period 1998-2009. The choice of the initial timeframe is related to the year in which the course started being taught at ISCED in Cabinda, integrated into the Cabinda University Centre (CUC), of Agostinho Neto University (UAN). The final milestone refers to the year of the ISCED framework at the 11 de Novembro University (UON) under Decree No. 7/09 of 12 May 2009, which established the reorganization of the Angolan higher public education institutions group. As research sources we used 13 interviews of professors and ISCED former students, produced with the oral history methodology, besides the written documentation of the course and undergraduate thesiswritten by its students from 2006 to 2009. The narratives recorded from the Oral history methodology, linked to written documents, enabled us to understand several questions about the history of Education in Angola and, specifically, aspects of the history of mathematics education in the country. Thus, taking perceptions and representations of the deponents as a starting point, we produce a history of the higher education establishment process in Cabinda and the first years of the start-up of the course designed to training mathematics teachers. In our analysis, we find that the creation of the center which offers the course occurred at a time of great sociopolitical instability, economic, educational and cultural of the country due to the long period - 27 years - of civil war. This context strongly affected the course during the first years of its operation, characterized by difficulties based on the lack of infrastructure, bibliographic materials and equipment, as well as difficulties of teaching mobility and availability of professors in terms of quality and quantity. The memories of students and professors also showed that the training of mathematics teachers at higher level in the province of Cabinda took place under urgency and shortage, leaving marks on the professors professional career and in academic training of former students.